Perceived myths and misconceptions about myocardial infarction among adults in Saudi Arabia - Alabdulmohsen, Dalal M.; Alotaibi, Nasser E.; Alshmrani, Layan S.; Alghamdi, Donia J.; Nehari, Khairiah I.; Al-Juraywi, Bushra I.; Almaazabi, Rehab F.; Alghamdi, Saja M.; Aljahdali, Shahad D.; Alsolami, Almas S.; Alkhalifah, Saleh A. (International Journal Of Community Medicine And Public Health, 2024)
Background: Myocardial infarction (MI), a widespread public health issue, is causing high mortality rates in Saudi Arabia. Good awareness about MI can improve outcomes for patients, and conversely, misconceptions can lead to delay in seeking treatment and affect patients’ compliance to preventive measures. Therefore, this study aims to assess the perception and beliefs of people in Saudi Arabia regarding myths about this issue. Methods: A cross-sectional survey using an online questionnaire was done in Saudi Arabia from October to November 2024 and included adults from both genders and various age groups. The questionnaire contained 10 common myths about MI, and a myth score of 10 points was established as 1 point given for each myth the participants agreed with. Results: The total number of participants was 951. About 74% were familiar with the term “heart attack,” and 70% acquired knowledge from the internet. The average myth score was 2.13±1.77 out of 10 total points. Approximately 25% of our study participants agreed with only one of the provided false statements, while less than 1% agreed with all ten. Conclusions: Overall, the study showed that most participants had good recognition of myths about myocardial infarction. There were links between myths belief and demographic factors like age and gender, in addition to health conditions such as diabetes and hypertension. Men and people with histories of strokes had the lowest levels of awareness compared to others. Correcting misconceptions is crucial to improve outcomes for patients at risk of MI.